Safety and Efficacy of Incorporating Actellic® 300 CS into Soil Wall Plaster for Control of Malaria Vectors in Rural Northeastern Uganda - Tonny Jimmy Owalla; Emmanuel Okurut; Kenneth Ssaka; Gonsaga Apungia; Barbara Cemeri; Andrew Akileng; Basil Ojakol; Mark J. I. Paine; Hanafy M. Ismail; Thomas G. Egwang (Tropical Medicine and Infectious Disease)
Indoor residual spraying (IRS) and the use of insecticide-treated bednets for malaria vector control have contributed substantially to a reduction in malaria disease burden. However, these control tools have important shortcomings including being donor-dependent, expensive, and often failing because of insufficient uptake. We assessed the safety and efficacy of a user-friendly, locally tailored malaria vector control approach dubbed “Hut Decoration for Malaria Control” (HD4MC) based on the incorporation of a WHO-approved insecticide, Actellic® 300 CS, into a customary hut decoration practice in rural Uganda where millions of the most vulnerable and malaria-prone populations live in mud-walled huts. Three hundred sixty households were randomly assigned to either the HD4MC (120 households), IRS (120 households) or control group without any wall treatment (120 households). Entomological indices were assessed using pyrethrum spray catching, CDC light traps and human landing catches. The Actellic® 300 CS toxicity on acetylcholinesterase activity among applicators of HD4MC was evaluated using the Test-mate (Model 400) erythrocyte acetylcholinesterase (AChE) test V.2, whereas toxicity in household occupants was monitored clinically. The Actellic® 300 CS level in house dust was analyzed using reversed-phase high-performance liquid chromatography (RP-HPLC). Entomological indices were compared between the three study arms at 1.5, 3 and 6 months post-intervention. HD4MC- and IRS-treated huts had a significantly reduced malaria vector density and feeding rate compared to control huts. There was no significant reduction in acetylcholinesterase activity at 1.5 and 24 h post exposure. Actellic® 300 CS exposure did not result in any serious adverse events among the household occupants. In conclusion, HD4MC was safe and had comparable efficacy to canonical IRS.